(untitled) (Aadim Journal of Multidisciplinary Research, 2025)
This paper examines the values of democracy and democratic governance, arguing that while many countries, including Nepal, have long practiced democracy, democratic systems alone are insufficient to ensure peace, development, and effective governance. It highlights how governments that do not prioritize democratic governance risk internal and external conflicts, as evidenced by ongoing conflicts in countries such as Ukraine and Russia, despite their democratic frameworks. By analyzing secondary literature on democracy, governance, and conflict, the paper contends that the quality and practice of democratic governance—beyond the mere existence of democratic institutions—shape the prospects for peace and development. Using governance indices and secondary data, the paper evaluates the successes and challenges of local democracy globally, with a particular focus on Nepal’s post-2006 democratic transformation. It finds that institutional structures, political participation, public accountability, and service delivery mechanisms have often fallen short of meeting the needs and aspirations of the people. Political instability, corruption, and weak institutional capacity continue to undermine effective democratic governance in Nepal and elsewhere. Additionally, the paper explores fiscal decentralization and federalism as important frameworks for improving economic efficiency, managing ethnic diversity, and addressing regional disparities. Drawing on classical theories such as Oates’ Theorem of Decentralisation and Tiebout’s model of local preferences, it emphasizes the benefits of tailoring public services to local contexts, especially in large, diverse countries. The Nigerian federal experience is discussed as a case study illustrating the persistent challenges of centralized power, ethnic tensions, and political instability despite constitutional reforms aimed at decentralization.